siMacro: A Fast and Easy Data Processing Tool for Cell-Based Genomewide siRNA Screens - Nitin Kumar Singh; Bo Yeun Seo; Mathukumalli Vidyasagar; Michael A. White; Hyun Seok Kim (Genomics & Informatics)
Growing numbers of studies employ cell line-based systematic short interfering RNA (siRNA) screens to study gene functions and to identify drug targets. As multiple sources of variations that are unique to siRNA screens exist, there is a growing demand for a computational tool that generates normalized values and standardized scores. However, only a few tools have been available so far with limited usability. Here, we present siMacro, a fast and easy-to-use Microsoft Office Excel-based tool with a graphic user interface, designed to process single-condition or two-condition synthetic screen datasets. siMacro normalizes position and batch effects, censors outlier samples, and calculates Z-scores and robust Z-scores, with a spreadsheet output of >120,000 samples in under 1 minute.